The Influence of Position Promotion and Transformational Leadership Style on Employee Turnover Intention - Krisna Sukma; Sri Sulistyawati; Sukana Sabudi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
An increased turnover can harm the company, especially in productivity, and increase costs. Turnover intention is a measurement of whether employees plan to leave their positions. Factors that can influence turnover intention are job promotions and transformational leadership styles. This study aims to determine the effect of job promotion and transformational leadership style on the turnover intention at Zia Kuta Hotel. Data collection used are interviews, documentation, and online questionnaires with a saturated sampling technique. Thirty-seven respondents were involved in this study except for General Manager. Data analysis used descriptive analysis and multiple regression analysis. The results indicate that job promotion and transformational leadership style negatively and significantly affect turnover intention. Job promotion and transformational leadership style simultaneously considerably affect employees' turnover intention. The results of the determination coefficient analysis, job promotion, and transformational leadership style have a 62.3% contribution.